Analisis Filogenetik Familia Ikan Kerapu Serranidae Berdasarkan Penandaan Chytocrome Oxydase I (COI) dari Pasar Ikan Lokal di Indonesia - Winda A. Fietri; Abdul Rajak; Ramadhan Sumarmin (Jurusan Biologi FMIPA Universitas Cenderawasih, 2021)
This research aims to explain the kinship or phylogeny of grouper fish of the Serranidae family based on Cytochrome Oxidase I (COI). Analysis based on previous research obtained type of grouper fish inhabiting Indonesian waters. A total of 39 grouper fish were collected from local fishermen. January-April 2014. Lombok (n=12 samples) in January, Karimunjawa (n=11) in May, Lampung (n=4) in February, Kendari (n=3) in January, Madura (n=3) in April, Tanakeke (n=3) in February, and Numfor (n=3) in May. From the results of the analysis using MEGA X software obtained the level of kinship between species tested very closely, among others species Epinephelus areolatus, E. merra, E. fasciatus, E. longispines, E. coioides, E. ongus, and E. coeruleopunctatus. The genetic average distance of all species is 0.02. In general, the association of species found is that several species are found in the same location with almost the same morphology and food. Key words: phylogenetic analysis; Serranidae family; grouper fish; COI markers.